PREMENSTRUAL SYNDROME DAN DYSMENORRHEA PADA SISWI SMAN 1 CANGKRINGAN, SLEMAN, YOGYAKARTA - , KHIFTIYAH HIKMAWATI; , Wiwin Lismidiati, S.Kep., Ns., M.Kep., Sp.Mat. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: In the menstrual cycle, some women have experienced premenstrual syndrome and dysmenorrhea. In general, the first action taken to overcome the pain suffered is to seek treatment. Health seeking behavior can be done by going to a health care or self treatment. Objective: This study aims to describe the health seeking behavior symptoms of premenstrual syndrome and dysmenorrhea at SMAN 1 Cangkringan and the factors that could influence health seeking behavior. Methods: This study used a cross-sectional design, subjects were 118 female students who had experienced symptoms of premenstrual syndrome and/or dysmenorrhea. Data obtained using SPAF questionnaire, VAS, and some questionnaires were adopted from previous research, the questionnaires are knowledge about menstruation and menstrual disorders, attitudes toward health seeking behavior, achieving accessibility of health services, family support, and health seeking behavior. Results: Bivariate analysis found a significant association between the level of dysmenorrhea, attitudes, and family support for health seeking behavior (p = 0.000, p = 0.005, p = 0.000). From the results of multivariate analysis, level of dysmenorrhea and family support most significant influence on health seeking behavior (p = 0.013 and p = 0.004). Most teenagers tend to go non-paramedics, such as herbal drink, rest, and do abdominal massage were the most frequent way to overcome the problems. Conclusions: Most of female student at SMAN 1 Cangkringan tend to go nonparamedics, herbal drink rest were the most frequent way to overcome the problems.